2009
DOI: 10.1111/j.1442-9071.2009.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic cyclophotocoagulation for the treatment of glaucoma: an Asian experience

Abstract: Endoscopic cyclophotocoagulation may have a treatment role in Asian patients with glaucoma. The success rate appears poorer than previously reported in Caucasian populations. The treatment effect appeared to wane between 18 and 24 months post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…In our study, there were no cases of hypotony, retinal detachment, and cystoid macular edema that have been previously reported. [2][3][4]7,14 Descemet's detachment in our study was secondary to an initial 1.8 mm incision for cataract surgery that occurred during insertion of the larger endoscopic probe. Hence, enlargement of the incision site is recommended for cataract surgery combined with ECP.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In our study, there were no cases of hypotony, retinal detachment, and cystoid macular edema that have been previously reported. [2][3][4]7,14 Descemet's detachment in our study was secondary to an initial 1.8 mm incision for cataract surgery that occurred during insertion of the larger endoscopic probe. Hence, enlargement of the incision site is recommended for cataract surgery combined with ECP.…”
Section: Discussionmentioning
confidence: 90%
“…2 An Asian study of ECP reported that 2 of 6 failures were in pseudoexfoliation patients, but did not specify how many pseudoexfoliation patients were included in their sample. 4 They 4 hypothesized that the failure in both cases of PXG could be because of the attenuation of the laser energy due to the pseudoexfoliative material, resulting in suboptimal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations